English Laboratory Management (A Site Study at SMP Semesta Semarang)) - Kusmaryuni, Ani (2012)
There are three objectives in this research are: (1) the characteristics of room management applied in English laboratory in SMP Semesta Semarang, (2) the characteristics of English lab materials in SMP Semesta, (3) the benefits of English laboratory in SMP Semesta Semarang. It is a qualitative research using ethnography design. The results of the research show: (1) Design of space in the language laboratory SMP Semesta Semarang using double separate table rows. Existing equipment in the lab of English instructor consoles among other, repeaters language learning machine, tape recorder, DVD player, video monitors, headsets and students booth mounted in a soundproof room. (2) The materials of lab are instructor console, repeaters language learning machine, tape recorder, DVD player, video monitors, headsets and students booth mounted in a soundproof room. Language Laboratory is a form of audio and video electronic devices consisting of instructor console as the main engine. It is also equipped with multimedia devices such as Tape Recorder, VCD / DVD player, there is also a repeater monitor or language learning machine. (3) English lab also has benefits for extracurricular activities. Extracurricular activities include Classic Speaking Club (ECC). ECC activities can be done in the lab. In SMP Semesta there are variety of extracurricular activities such as journalism, photography, theater, Home Public Speaking, etc.. Home Public Speaking is extra-curricular activities about English usage. Given the expected extracurricular English language skills will increase the student. In addition there is also a component of a multimedia computer as an additional component that can be combined with other apparatus. When it is fixed, the language lab and lab equipment as a multimedia language laboratory were built.